Implementation of Value Management for the Project Success - Abinaya . P*; Selvendiran S.G; Surya Raj Kumar (International Journal of Architectural Design and Planning, 2023)
Value management plays an important role in the quality, cost, and functionality of any construction project. The article examines the various applications of value management by examining the methods and techniques in the construction industry. This article examines the various factors involved in the strategies to increase the value of the project and the factors affecting project success. The analysis of the factors was listed according to the priority matrix, and major factors are highlighted based on value for money, quality, and functionality. A questionnaire survey was conducted to know the views of the construction professionals working on methods of value management in the construction industry.
Keywords: Value management; construction industry; correlation matrix; key factors; success